Aqueous electrospun core/shell nanofibers of PVA/microbial transglutaminase cross-linked gelatin composite scaffolds - ŞENGÖR, MUSTAFA; GÜNDÜZ, OĞUZHAN (ELSEVIER, 2020)
This study aims to produce gelatin-containing nanofibers in situ cross-linked with microbial transglutaminase (mTG) without using toxic, expensive small-molecule cross-linkers or solvents. Dynamics of enzymatic cross-linking activity was assessed with different enzyme concentrations. Possible time intervals for electrospinning of gelatin-mTG solutions were determined. Gelatin-mTG solution was electrospun as a shell on polyvinyl alcohol core nanofibers and the mTG concentration was optimized to obtain uniform, bead-free nanofiber morphology. For gelatin-mTG solutions, viscosity values below similar to 9.5 centipoise (cP) allowed electrospinning. An mTG concentration of 0.5% (wt/wt) sustained viscosity levels that allow electrospinning for 240 min. Cross-linking activity of mTG was determined by physical and chemical characterization of obtained nanofibers. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Core shell nanofiber; Microbial transglutaminase; Aqueous electrospun; Green electrospinning; Biomaterials; Nanocomposites